ENVIRONMENTAL IMPACT ANALYSIS FOR HEALING MENTAL HEALTH PATIENT - Unix Cahya Husada; Catharina Louise; Anabella Markes; Dwi Saputro; Asih Setyaning Bekti; Sri Andarini (Universitas Brawijaya, 2022)
Background : Mental health is a condition in which individuals can develop physically, mentally, spiritually, and socially so that they are aware of their abilities, can cope with pressure, work productively and are able to contribute to their community. According to the Indonesian Ministry of Health (2016), there are around 35 million people affected by depression, 60 million people affected by bipolar, 21 million affected by schizophrenia, and 47.5 million affected by dementia, psychosocial, religious, cultural and environmental. Several factors that affect mental health are social life, such as the family environment, school/work, and the social environment in general. Patients with mental health disorders have a calm tendency to be in a safe and comfortable environment. The physical environment for mental health patients is a safe and comfortable environment prepared to provide social impact for people with mental health conditions in hospitals. Facilities that must be prepared to support the healing environment process include privacy, social support, and a positive impact on the environment. This writing employs a literature review method related to the topic Environmental Impact Analysis for healing mental health patients. There are 14 journals used in this writing. The purpose of this paper is to analyze the environment that has an impact on the process of treating and healing patients with mental health disorders. Method : This study uses a literature review method related to the topic Environmental Impact Analysis for healing mental health patients . Literature review has an important role in making a scientific paper or essay, because it can provide ideas and goals about the research topic to be carried out which is about how the environmental impact for healing mental health patients. Conclusion : The social environment can be a source of mental health disorders, if not managed properly, as well as physical environmental factors. A well-managed social and physical environment can support healing . Health facilities as role models should apply the concept of a social environment and physical environment that supports and impacts on patient healing. Keywords: mental health, physical environment, social environment